The importance of in-situ conservation area in mining concession in preserving diversity, threatened and potential floras in East Kalimantan, Indonesia - ABBAN PUTRI FIQA; FAUZIAH FAUZIAH; DEWI AYU LESTARI; SUGENG BUDIHARTA (Biodiversitas Journal of Biological Diversity, 2019)
Fiqa AP, Fauziah, Lestari DA, Budiharta S. 2019. The importance of in-situ conservation area in mining concession in preserving diversity, threatened and potential floras in East Kalimantan, Indonesia. Biodiversitas 20: 198-210. East Kalimantan is the most well-known province in Indonesia with high natural resources, particularly from the mining sector. While delivering benefits for economic development, coal mining operation negatively affects biodiversity. Effort to mitigate impacts on biodiversity is by establishing an in-situ conservation area inside the coal mining area. This area is preserved in the form of arboretum from existing natural forests. The aim of this research is to identify the importance of conservation area in a mining concession in East Kalimantan regarding its plants’ diversity, conservation status, and utilization. The research was conducted by doing vegetation analysis and inventorying plant biodiversity inside the in-situ conservation area by using plot samples. The result showed that the in-situ conservation area protects at least 142 species with a high level of biodiversity on all vegetation phases, indicated by Shannon Wiener diversity indices in which all phase have an index higher than 3. It protects 22 species listed in IUCN Red List of threatened species and contains at least 90 potential plants utilized by traditional Dayak people in their daily life. This study highlights that the conservation area is an important part in mining management to protect biodiversity, and suggest that in-situ conservation area should be preserved by every mining concession.